Learning English Out of School: An Inclusive Approach to Research and Action - Moore, Emilee; Vallejo, Claudia (Foreign Language Teaching in Europe, 2021)
This volume reports on the main results of the research project Inclusive epistemologies and practices of out-of-school English learning. The study reacts to low attainment levels in English as a foreign language among socioeconomically disadvantaged youth. The contributors to this volume research teenagers' existing practices of using and learning English out of school time and implement new, inclusive, nonformal English language educational initiatives. They evaluate the impact of the nonformal English language educational initiatives implemented and support their sustainability and transferability. The project embeds collaborative and arts-based methods into its methodology, fostering inclusive and creative educational practices and ways of knowing.